Digital Transformation of Islamic Religious Education: Integrating Artificial Intelligence and Religious Moderation in Inclusive Islamic Religious Education Learning - Syafril Barus; Fathul Jannah (Indo Green Journal, 2026)
The digital transformation of Islamic Religious Education (PAI) has created new opportunities and challenges in the learning process, particularly through the integration of artificial intelligence (AI). This study aims to analyze how AI can be responsibly integrated into inclusive PAI learning to strengthen religious moderation, academic integrity, and data literacy. This research uses a library research method with a qualitative descriptive approach, reviewing relevant scholarly literature, journal articles, policy documents, and institutional reports on AI in education, Islamic Religious Education, inclusive learning, religious moderation, plagiarism risk, and teacher-student readiness. The results show that AI has the potential to support PAI learning through personalized instruction, adaptive learning materials, accessibility features, formative feedback, and digital engagement. However, AI integration also raises ethical concerns, including plagiarism, overreliance on technology, misinformation, algorithmic bias, and weak spiritual formation. Therefore, AI should be positioned as a learning assistant rather than a substitute for teachers. The study emphasizes that inclusive AI-based PAI learning must be grounded in Islamic ethical values and religious moderation, including tolerance, balance, justice, non-violence, and respect for diversity. The novelty of this study lies in its integrative conceptual framework that connects responsible AI use, religious moderation, academic integrity, data literacy, and inclusive Islamic education. This study recommends that schools and madrasahs develop clear guidelines for AI use, strengthen teachers' competence, and design reflective assessment models that promote honesty, critical thinking, and responsible digital citizenship